Фонетическaя природa ротaцизмa в чувaшском языке (Journal of Oriental Studies, 2018)
The Turkic languages have long been found very interesting is the phoneticphenomenon of rhotacism. Nature phonetic matching r ~ z is one ofthe most mysterious phenomena in Turkic studies. Phonetic phenomenonrhotacism still remains a controversial issue in linguistics. In this article theauthor comments on a number of different hypotheses and tries to uncoverits meaning.